Determining the dynamic amplification factor of multi-span continuous box girder bridges in highways using vehicle-bridge interaction analyses. (15th February 2019) - Ma, L.; Zhang, W.; Han, W.S.; Liu, J.X.
Highlights: The impact factors (IMs) of continuous beam bridges increase dramatically when resonance phenomena occur. Vehicle-bridge resonance is closely related not only to vehicle frequency and bridge frequency but also to the disturbance frequency caused by vehicle movement. Travelling velocity exerts an important influence on resonance. In most cases, the IM of a continuous beam bridge reaches its peak at a low travelling velocity. Vehicle-bridge resonance may be caused by the first-order mode or the second-order mode of a bridge. Second-order curvature modes exert an especially crucial influence on the IMs of the negative moment at the interior supports. The maximum IM of continuous beam bridges at the interior supports is much larger than the maximum IM at the mid-spans, which is an important feature of the IMs of continuous beam bridges. For the VM at the interior supports, the maximum DAF may be more than 1.7. If the design vehicular load specified in AASHTO code is used, the DLA of 33% is applicable to the force effect at the supports. However, when the same static traffic load standard is applied to both interior supports and mid-spans, a DLA of 75%, which is used for the deck joint in AASHTO code (2017), is necessary for the moment effect at interior supports. Abstract: The impact factors of multi-span continuous box girder bridges in highways are influenced by many factors, including road roughness, vehicle-bridge interactions (VBIs), and travelling velocity. Currently, the empirical formulas specified by bridge design codes are based on single factors (bridge length or fundamental frequency). These formulas yield inconsistent results that can differ widely. In this paper, the regularity of the dynamic amplification factors (DAFs) of continuous beam bridges is investigated by selecting 15 continuous beam bridges and conducting VBI analyses. The results indicate that the DAFs of the continuous beam bridges increase dramatically when resonance phenomena occur. The vehicle-bridge resonance is closely related to vehicle frequency, bridge frequency and the disturbance frequency caused by vehicle movement. The travelling velocity exerts an important influence on the resonance. In most cases, the DAF of a continuous beam bridge peaks at the velocity range of 40–60 km/h. Vehicle-bridge resonance may be caused by the first-order or second-order mode of a bridge. Second-order curvature modes exert an especially crucial influence on the DAF of the negative moment at the interior supports. The empirical formulas used in current bridge design codes fail to account for the influence of resonance and travelling velocity on the DAFs of bridges. The maximum DAF at the interior supports of the continuous beam bridges may exceed 1.7.